Respuesta :
Answer:
-6 and -7 are the roots
Step-by-step explanation:
The quadratic equation given is:
[tex]x^{2}+13x=-42\\Taking\ -42\ to\ left\ hand\ side\ we\ get\\x^{2} +13x+42=0[/tex]
We can factorise the equation as:
[tex]x^{2}+6x+7x+42=0\\(x^{2}+6x)+(7x+42)=0\\[/tex]
Taking x common from the first bracket and 7 common from the second bracket we get:
[tex]x(x+6)+7(x+6)[/tex]
Taking (x+6) common from both terms we get:
[tex](x+6)(x+7)=0[/tex]
x= -6 or x=-7
Hence -6 and -7 are the roots of the given quadratic equation.